The impact of age on oncogenic potential: tumor‐initiating cells and the brain microenvironment. Issue 5 (28th June 2013) - Stoll, Elizabeth A.; Horner, Philip J.; Rostomily, Robert C.
Summary: Paradoxically, aging leads to both decreased regenerative capacity in the brain and an increased risk of tumorigenesis, particularly the most common adult‐onset brain tumor, glioma. A shared factor contributing to both phenomena is thought to be age‐related alterations in neural progenitor cells (NPCs), which function normally to produce new neurons and glia, but are also considered likely cells of origin for malignant glioma. Upon oncogenic transformation, cells acquire characteristics known as the hallmarks of cancer, including unlimited replication, altered responses to growth and anti‐growth factors, increased capacity for angiogenesis, potential for invasion, genetic instability, apoptotic evasion, escape from immune surveillance, and an adaptive metabolic phenotype. The precise molecular pathogenesis and temporal acquisition of these malignant characteristics is largely a mystery. Recent studies characterizing NPCs during normal aging, however, have begun to elucidate mechanisms underlying the age‐associated increase in their malignant potential. Aging cells are dependent upon multiple compensatory pathways to maintain cell cycle control, normal niche interactions, genetic stability, programmed cell death, and oxidative metabolism. A few multi‐functional proteins act as 'critical nodes' in the coordination of these various cellular activities, although both intracellular signaling and elements within the brain environment are critical to maintaining a balance between senescence and tumorigenesis. Here, we provide an overview of recent progress in our understanding of how mechanisms underlying cellular aging inform on glioma pathogenesis and malignancy.